Znamčenje kot spodbuda za razvoj zavarovanih območij - Logar, Erik (Geografski vestnik, 2024)
Nature parks represent special areas for preservation of natural and cultural heritage. Due to their conservationregime, they could become spaces of innovation. In Slovenia, with aim of promoting territorial development,approach of branding area was implemented in Goričko Nature Park. This contribution analyzes the devel-opment of branding process as a case study. Results show that it is important to establish cooperation andnetworking among providers in the area and to raise awareness of the strategic advantages of their loca-tion. The evaluation of implementation of branding in the park shows positive effects: strengthening cooperationamong providers, developing a common identity, and improving promotion and sales opportunities, but italso highlights challenges related to spatial inequality and limitations of funding and organization.
Keywords: Goričko Nature Park; Oblikovanje blagovne znamke; place branding; protected areas; regional planning; Regionalno planiranje; Zavarovana območja